2011
DOI: 10.4314/ijbcs.v5i1.68109
|View full text |Cite
|
Sign up to set email alerts
|

Caractérisation morphométrique de l’abeille <i>Apis mellifera</i> adansonii au Nord-Est du Bénin

Abstract: L'analyse des indices cubitaux a montré qu'en dehors des abeilles de Dabou qui avaient une valeur moyenne de 2,28 ± 0,35, les abeilles de toutes les autres localités avaient des indices inférieurs à 2,10. Les résultats ont montré que les abeilles peuvent être classées selon la valeur de leur indice cubital, en trois groupes assez distincts. Cette étude ayant révélé une variation significative dans les caractères morphométriques de l'abeille au Nord-Est du Bénin, il importe d'adopter des stratégies appropriées … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
(8 reference statements)
2
3
1
3
Order By: Relevance
“…We found that the high wing length amplitude (7 mm-8.5 mm), the total leg length (6 mm -7 mm) and the cubital index (1.04-3.7) corresponded with those found in earlier studies (Amakpe, 2010;Paraïso et al, 2011). The high amplitude in the morphometric parameters was characteristic for honey bees from the Democratic Republic of Congo to Senegal, which belong to the adansonii subspecies (Franck et al, 2000a;Ruttner, 1988).…”
Section: Morphometric Diversity In the Honey Beessupporting
confidence: 86%
See 1 more Smart Citation
“…We found that the high wing length amplitude (7 mm-8.5 mm), the total leg length (6 mm -7 mm) and the cubital index (1.04-3.7) corresponded with those found in earlier studies (Amakpe, 2010;Paraïso et al, 2011). The high amplitude in the morphometric parameters was characteristic for honey bees from the Democratic Republic of Congo to Senegal, which belong to the adansonii subspecies (Franck et al, 2000a;Ruttner, 1988).…”
Section: Morphometric Diversity In the Honey Beessupporting
confidence: 86%
“…The honey bees in the Republic of Benin were classified as A. mellifera adansonii based on morphometric measurements by Villières (1987). Further studies were limited to measurements of key body parts in isolated villages located in the centre and the north of the country and provided no further characterization (Amakpe, 2010;Hounpke et al, 2007;Paraïso et al, 2011, Paraïso et al, 2017. Morphological characterization is still considered as a very important method in the classification of honey bees with more than forty useful parameters (Adl et al, 2007;Fresnaye, 1981;Meixner et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Les longueurs moyennes des abeilles, prélevées au cours de notre étude varient de 12,47 ± 0,80 mm à 13,60 ± 0,91 mm. Ces valeurs sont supérieures à celles obtenues par Paraïso et al (2011) dans le nord-est du Benin chez la sous-espèce Apis mellifera adansonii dont les longueurs des abeilles variaient de 10,86 mm à 11,97 mm. Par ailleurs les résultats montrent que les individus sont plus grands au sud où le climat est plus humide et deviennent plus petits au nord où le climat est plus sec.…”
Section: Discussionunclassified
“…Cette variation dans la population indique que les abeilles prélevées appartiennent à des écotypes différents. Une variabilité similaire a été observée chez des abeilles voisines au Benin par Paraïso et al (2011) qui ont observé la présence de 3 groupes distincts d'abeilles dans la population étudiée.…”
Section: Discussionunclassified
See 1 more Smart Citation